Student readiness on using web-based resources: a case study / Peridah Bahari, Salina Hamed and A'bas Ismail - Bahari, Peridah; Hamed, Salina; Ismail, A'bas (Research Management Institute (RMI), 2007)
The widespread acceptance of Web Technology in our tertiary institutions has brought about changes in the style, quantity and variety of resources that are made available to students. Fundamentally new learning environment is provided for students. On the other hand, there is still question about student readiness in using the abundant resources made available to them on the Web. This study examines students' readiness in using web-based resources. Variables that were look into are demographic background, level of technology usage, level of computer resources usage and their perspective on technology. 621 questionnaires were distributed randomly to diploma and degree engineering students (electrical, mechanical and civil). Based on students' ability on using web-based resources, result obtained from quantitative data showed there was a significant difference between student from different semesters (F = 4.264, p = 0.0), type of accommodation (t = -2.233, p = 0.0), and family income (t = -2.453, p = 0.014). Weak correlations were found between student's ability and students' expertise, students' opinion, students' knowledge and regularity in computer usage.